Procrastination during the COVID-19 Pandemic: A Scoping Review - Alejandro Unda-López; Gabriel Osejo-Taco; Andrea Vinueza-Cabezas; Clara Paz; Paula Hidalgo-Andrade (Behavioral Sciences, 2022)
Procrastination involves voluntarily or habitually delaying unpleasant tasks for later. It is characterized by short-term benefits and long-term costs. The COVID-19 pandemic set specific circumstances that may have influenced procrastination behavior. This scoping review identified the existing peer-reviewed literature in English or Spanish about procrastination during the COVID-19 pandemic (January 2020 to April 2021) in six electronic databases. To conduct the review, a five-step methodological framework, as well as established PRISMA guidelines, was followed. A total of 101 articles were found. After removing duplicates and reviewing the articles, only 13 were included in the review. Findings indicate that procrastination was studied mostly in academic contexts in various parts of the globe. Procrastination behavior was related to anxiety, distress, time management, self-control, and other variables. There is limited information about interventions to prevent or decrease procrastinating behaviors in the context of confinement or in the living conditions generated by the pandemic. Future research should consider how procrastination evolved during the pandemic using longitudinal methodologies. Individual differences related to procrastination also should be identified, and the evaluation of the efficacy of existing interventions is still needed. This information might help in the creation of appropriate interventions that target detrimental procrastination behaviors.